2015
DOI: 10.1155/2015/751293
|View full text |Cite
|
Sign up to set email alerts
|

Unprotected Left-Main Coronary Angioplasty in the Elderly in a High Volume Catheterization Centre without On-Site Surgery Facilities: Immediate and Medium Term Outcome—The Old-Placet Registry

Abstract: We aim to assess clinical feasibility and efficacy of unprotected left main (ULM) percutaneous coronary intervention (PCI) in patients older than 75 years over a 6-year period and with 2-year follow-up demonstrating that PCI is a feasible revascularization strategy even in absence of on-site cardiothoracic support. Nevertheless, the outcome of these high-risk patients is still hampered by a sensible in-hospital mortality rate. Older patients have a higher mortality at follow-up (10.0 versus 0.8%, P = 0.014), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
6
2
1
Order By: Relevance
“…(2,5) Similarly, Gagnor et al also reported that the rate of adverse events in patients after discharge was low. (6) However, the Kaplan-Meier survival curve did not show similar results in the present study. This may be related to differences in follow-up time.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…(2,5) Similarly, Gagnor et al also reported that the rate of adverse events in patients after discharge was low. (6) However, the Kaplan-Meier survival curve did not show similar results in the present study. This may be related to differences in follow-up time.…”
Section: Discussioncontrasting
confidence: 80%
“…In the study by Parma et al, follow-up time was 15.8 ± 10.9 months, with a median of only 14 months. (5) The follow-up times of the studies carried out by Izumikawa et al and Gagnor at al were also only 1.7 ± 2.9 years and 504 ± 653 days, respectively, (2,6) which was substantially shorter than the follow-up time in the current study, which was 44.6 ± 31.3 (median 60) months.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Reviewing the literature, there is a worldwide variety in the management of PPCI of ULMCA concerning drug-eluting stent (DES) or bare metal stent (BMS) use. Most of the contemporary European, Australian and Japanese studies reported dominant BMS8 17 or mixed BMS/DES1 3 16 18 21 use, while in the Korean studies, most PPCIs of the ULMCA were performed with DES 9 14 19. Previous large meta-analyses comparing DES with BMS in patients with stable angina/acute coronary syndromes38 and STEMI39 consistently showed no benefit of DES concerning death or MI, whereas revascularisation rates were significantly lower with DES.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies demonstrated a relatively high in-hospital mortality despite successful primary PCI in the subset of the population, which ranged from 16-38%. [24][25][26][27] The LM as infarct artery without collateral branches or a coronary bypass graft usually causes a large area of ischemia and deteriorates the left ventricular function. Afterwards, cardiac function is susceptible to a second strike as soon as the coronary flow recovers, namely reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%